New Approaches to Qur'anic Hermeneutics in the Muslim World - Albayrak, Ismail; Coruh, Hakan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, titled "New approaches to Qur'anic hermeneutics in the Muslim world", discusses the approaches that play significant roles in modern Qur'anic interpretation in the Islamic world. The eleven articles in this reprint demonstrate the richness of resources in Qur'anic hermeneutics in the Muslim World. The authors from different backgrounds and regions have made a great contribution to Qur'anic studies and hermeneutics in the modern period. The following topics are covered throughout the reprint: Decolonizing Qurʾanic Studies, contextualist approach in the modern period and its theoretical origins in the classical Islamic scholarship, Qur'an hermeneutics and historicism (or contextualism in western context) in contemporary Turkey, transempirical exegesis in Said Nursi's Risale-i Nur Collection, Fādil al-Samarrā'ī's (b. 1933) contribution to literary and rhetorical Qur'anic exegesis, Shia scholar Ayatollah Yusuf Sanei's (d.2020) broader jurisprudential approach, Comparative Theology and comparative readings (isrā'īliyyāt and direct Bible citations) in Qur'anic exegesis with special reference to the narrative of Prophet Yaḥyā (John the Baptist) in the Qur'an and the Bible, critique of the concept of naskh (abrogation) in contemporary Qur'ānic hermeneutics (Naṣr Ḥāmid Abū Zayd's critique), thematic interpretation (tafsīr mawḍū'ī) in Indonesia in the 2000s, inclusive Islamic interpretations in the light of rationalistic Maturidite theology, and violence and jihad in Islam: From the war of words to the clashes of definitions.